Usability and Navigability of an HIV/AIDS Internet Intervention for Adolescents in a Resource Limited Setting - Ybarra, Michele (2012)
Use of Internet is growing in Sub Saharan Africa. Evidence of computer and Internet effectiveness for reduction in risk behaviors associated with HIV shown in U.S. settings has yet to be replicated in Africa. We describe the development, usability and navigability testing of an Internet-based HIV prevention program for secondary school students in Uganda, called CyberSenga. For this work, we used four data collection activities, including observation of (a) computer skills and (b) navigation, (c) focus group discussions, and (d) field assessments to document comprehension and usability of program content. We document limited skills among students, but youth with basic computers skills were able to navigate the program after instruction. Youth were most interested in activities with more interaction. Field-testing illustrated the importance of using a stand-alone electrical source during program delivery. This work suggests delivery of Internet-based health promotion content in Africa requires attention to user preparedness and literacy, bandwidth, Internet connection, and electricity.